Tindak Pidana Penggunaan Ganja Untuk Keperluan Pengobatan - Ronaldo Semmy Kaya; Deassy Jacomina Anthoneta Hehanussa; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: This study discusses cannabis which is used as a medicinal ingredient.Purposes of the Research:  analyze adn explain the qualificationof marijuana used as a crime and analyze and explain thr policy of cannabis formulation for medicinal puerpuseMethods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of  legal regulations, scientific papers and literatureResults of the Research: The results of the study indicate that the use of marijuana for medicinal purposes can be subject to criminal penalties as it is known that marijuana is a class I narcotic besides Article 37 of Law Number 35 of 2009 stipulates that only Narcotics Groups II and III can be used as medicinal ingredients. Furthermore, Article 53 of Law Number 35 of 2009 regulates the use of Narcotics II and III in limited quantities to be used as treatment materials. However, class I narcotics are not allowed to be used as any medication. That means those who store, distribute and use marijuana can be punished.